KURSUS SINGKAT DAN PELATIHAN PEMANFAATAN PEPAYA (CARISA PAPAYA L.) MENJADI MANISAN KERING BUAH PEPAYA DI DESA TIMUHUN, KECAMATAN BANJARANGKAN, KABUPATEN KLUNGKUNG - I Made Nada; Ni Nyoman Sulastri; I Putu Gede Budisanjaya; Gede Arda (Buletin Udayana Mengabdi, 2008)
ABSTRACT In Desa Timuhun, eventhough papaya is not primary fruit product, but usually papaya is planted among the other plants and easily to grow. Papaya has good potency to be processed to become food product. Matured papaya fruit is usually fresh served for desk fruit. On the other hand, for papaya which is not mature yet, usually used for vegetable. Papaya has high water content, so it makes papaya fruit easy to experience damage. With papaya processing, papaya which is originally assumed improper to be sold or to be consumed (mechanical damage, diseased, acid, physical damage) and will only to be thrown, finally can be used. The making of papaya dry candy is one of effort to preserve and to vary form of papaya serving. It also improves the economic value of papaya. The making of papaya can be conducted in big or small scale. The activity objectives are to introduce and give additional knowledge to society about papaya processing technology, to increase economic added value of papaya and the using of papaya which is improper to be sold or to be consumed becoming valuable food product .Realization of the objectives above are by performing an information sharing and discussion with the society about process of the making dry candy from papaya, training of papaya dry candy making, introduce simple technology of dry candy papaya making. This activity was performed at the head of Desa Timuhun office, on Friday, September 14, 2007 and was attended by 26 persons, including association of woman farmer and the staff in that office. The result of this activity shows that there was positive response of people who attend this activity, because by processing papaya fruit into dry candy, have a lot of advantage compare to sale it freshly. Beside that, this dry candy is healthy snack, without synthetic preservation, enriched with vitamins which is useful for health, also this dry candy is still good up to 1 month and of course it could to improve economic value compared to be sold freshly